Comparisons of tactical and technical performance factors between winners and non-winners in Para Taekwondo: A comprehensive analysis of the 2020 Tokyo Paralympic Games - Park, C. H.; O`Sullivan, D. M.; Kim, M. S.; An, Y. J.; Jung, H. C. (Journal of Sports Sciences, 2024)
This study aims to analyse the differences in tactical and technical elements between winners and non-winners and identify key strategic and technical elements contributing to performance in Para Taekwondo. Notational analysis was used to achieve these objectives, and 78 Para Taekwondo matches (36 men`s matches and 42 women`s matches) from the 2020 Tokyo Paralympics were analysed. The recorded videos were analysed using Adobe Premiere Pro software (version 24.2) with a frame-by-frame analysis of 0.033 seconds. The main results are: a) winners had significantly higher kick-to-score ratios compared to non-winners (male: 38.3 ± 17.37% vs. 19.4 ± 11.95%, p < .001; female: 32.7 ± 18.17% vs. 11.0 ± 7.72%, p < .001); b) winners had fewer attack attempts but higher scoring efficiency; c) non-winners used the front leg more frequently (male: 43.2% vs. 39.7%, p < .05; female: 47.5% vs. 42.7%, p < .001); d) logistic regression analysis showed that kick-to-score ratio significantly impacted match outcomes for both male (OR = 1.10, p < .001) and female athletes (OR = 1.19, p < .001), while offensive frequency negatively impacted female athletes` match outcomes (OR = 0.89, p = .002). This study emphasizes the importance of scoring efficiency and strategic defensive actions, consistent with patterns in Olympic Taekwondo. It provides insights for enhancing athlete training and match strategy in combat sports, enriching the understanding of Para Taekwondo.